1976
DOI: 10.1037/0022-0167.23.6.532
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of empathic listening in telephone counseling.

Abstract: Two counseling-analogue studies compared empathic-listening and active advice-giving styles of telephone counseling with college undergraduate participants. Nonsignificant trends of preference for the advice-giving style in Study 1 led to the comparison in Study 2 of these same styles with a third, combined counselor role. Results consistently indicated significant participant preference for active advice giving on overall call evaluation and on the two major factors (Helpfulness of Call and Helper Likability)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
7
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
4
7
0
Order By: Relevance
“…Although active listening resulted in greater conversational satisfaction and social attraction than simple acknowledgements, active listening and advice giving produced statistically equivalent levels. These findings bear some similarity to other studies comparing active listening and advice (e.g., Libow & Doty, 1976;Scholl, 2002). Given the similarity in results for hypotheses 2 and 3, taken together, research is beginning to suggest that people respond to listeners' overall level of responsiveness regardless of the form it takes.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Although active listening resulted in greater conversational satisfaction and social attraction than simple acknowledgements, active listening and advice giving produced statistically equivalent levels. These findings bear some similarity to other studies comparing active listening and advice (e.g., Libow & Doty, 1976;Scholl, 2002). Given the similarity in results for hypotheses 2 and 3, taken together, research is beginning to suggest that people respond to listeners' overall level of responsiveness regardless of the form it takes.…”
Section: Discussionsupporting
confidence: 72%
“…Besides contradictory studies in the marital research (see below), two studies contradict D'Augelli and Levy's (1978) study comparing active listening and advice. In one study, volunteer telephone crisis counselors offering advice were rated more helpful and likeable than counselors responding with empathic (or active) listening (Libow & Doty, 1976). In a second study, Scholl (2002) reports college academic counseling clients preferred receiving advice rather than active listening responses early in counselor-client relationships.…”
Section: Comparative Advantages Of Active Listeningmentioning
confidence: 98%
See 1 more Smart Citation
“…Advice may provide information (Barbee & Cunningham, 1995;Cutrona & Russell, 1990), enhance perceived control (Albrecht, Adelman, & Associates, 1987), and convey caring (Goldsmith & Fitch, 1997), but it can also be seen as critical or controlling (Goldsmith & Fitch, 1997), and can convey that the speaker wishes to solve the hearer's problem and move on to other topics (Pearlin & McCall, 1990). Not surprisingly, there are conflicting results of research on recipients' reactions to advice about a problem: Some studies find recipients expect and appreciate advice (Barnett & Harris, 1984;Libow & Doty, 1976;Reisman & Yamokoski, 1974), whereas other studies report negative reactions to advice (Dunkel-Schetter, Blasband, Feinstein, & Herbert, 1992;Lehman, Ellard, & Wortman, 1986;Notarius & Herrick, 1988;Pearlin & McCall, 1990).…”
mentioning
confidence: 99%
“…Peer counseling has increasingly become a vital part of the human service delivery system (Giddan & Austin, 1982;Pietrofesa, Hoffman, Splete, & Pinto, 1978). Investigations of the communication among peers discussing personal problems have typically indicated that empathic responses are viewed by college students as less desirable than more instrumental modes of response, such as active advice giving (e.g., Libow & Doty, 1976;Reisman & Yamokoski, 1974; for an exception to this finding, see Venzor, Gillis, & Beal, 1976). For example, Libow and Doty (1976) reported that analogue clients of a telephone counseling hotline preferred peer counselors who provided' direct advice to those who either offered nondirective empathic responses or a combination of advice giving and empathic responses.…”
mentioning
confidence: 99%